End of the innocents: engagement and decolonization in the Global South since 1968. Issue 3 (2nd September 2018) - Webster, David
ABSTRACT: Canada has approached the Global South (Third World) through colonial systems, as participants in British imperial structures. Canadians have seen themselves as being quite different in foreign affairs from the United States – a belief reflected in much of the literature about Canada's international history. In at least one way, this is accurate: Canadian governments have aimed to engage rather than isolate regimes seen as American adversaries. Yet Canadian policies toward decolonization echoed those of the colonial powers and differed little from American policies. With a focus on the governments of Pierre Trudeau, Brian Mulroney and Jean Chrétien, this article examines Canadian engagement strategies with China and Cuba and its hesitant approaches to decolonization in the British Empire, Portuguese Africa, Timor-Leste and elsewhere, concluding that Canada's diplomatic self-image diverges sharply from its actions.